Teaching the Philosophy of Practice as a Key Component of Pharmaceutical Care Practice - Keri Hager; Claire Kolar, Pharm.D., Ph.D.; Victoria Losinski, Pharm.D., Ph.D. (INNOVATIONS in Pharmacy, 2018)
No abstract required